Assessment of a novel nanostructured flocculant with elevated flocculation and antimicrobial activity. (January 2020) - Chen, Wei; Rong, Xiang; Peng, Jiujing; Tang, Qian; Luo, Hongbing; Fan, Liangqian; Feng, Keqin; Zheng, Huaili
Abstract: In this work, a novel process involving the preparation of nanochitosan-grafted flocculants (CPAM-g-NCS) to treat low turbid and salmonella suspensions simultaneously was introduced. Nanotechnology was employed to enhance the adsorption–adhesion and sterilization abilities of dual-functional flocculants. The monomers of chitosan, acrylamide, methacryloyl ethyl trimethyl ammonium chloride, and sodium tripolyphosphate were utilized for flocculants copolymerization. Then, using fourier-transform infrared spectroscopy, nuclear magnetic resonance hydrogen spectrum, and thermogravimetric and differential scanning calorimetry analysis, the successful synthesis of CPAM-g-NCS was verified. Scanning electron microscopy and size analysis suggested that nanostructured flocculants with irregular morphology and nanocolloids of 60.44 nm were formed. CPAM-g-NCS was applied to treat a series of simulated low turbid and salmonella suspensions. The simulation results showed that the minimum residual turbidity of 1.97 NTU and optical density of 0.16 (initial 0.89) can be achieved at dosages of 2.5 and 8.75 mg L −1, respectively, which were superior to conventional organics flocculants. Mechanistic studies suggested that the excellent adsorption property, and large numbers of quaternary ammonium and amino groups of nanoflocculants contributed to the superior flocculation and antibacterial performance of CPAM-g-NCS. Graphical abstract: Image 1 Highlights: A novel dual effect nano flocculant CPAM-g-NCS was successful synthesized. CPAM-g-NCS showed efficient dual functionality of flocculation and antibacterial. Nanostructure of CPAM-g-NCS elevated the absorption ability of flocculants. The sterilization action of CPAM-g-NCS was definitely bactericidal.